Evaluation of Quality of Life After Inflatable Penile Implantation and Analysis of Factors Influencing Postsurgery Patient Satisfaction. Issue 9 (3rd August 2022) - Luna, Eusebio; Rodriguez, Dayron; Barrios, Dailianys; Hernandez, Hunter; Bianco, Fernando; Gheiler, Edward
ABSTRACT: Background: Most of the published literature addressing the satisfaction postinflatable penile implant (IPP) placement includes non-validated surveys. Aim: The study aims to report the survey outcomes of the English version of The QoLSPP and to evaluate the different factors that could influence these results. Methods: Patients who underwent inflatable penile implant placement from January 2017 to December 2019 received a survey by phone and had a visit scheduled no sooner than 27 months after surgery. In the clinic, they were inquired about the penile size and underwent measurements of postoperative penile length and diameter. The survey responses were rated from zero to 5 following QoLSPP, and answers ≥3 were considered positive. An evaluation of the factors influencing the quality-of-life score of patients post-IPP placement was performed. Variables included age (<60, 60–70, >70), BMI classification, Charlson Comorbidity Index, diabetes diagnosis, implant type (AMS 700CX vs Titan), ED etiology, revisions, postoperative time in months (<30, 30–40, >40) and preoperative vs postoperative penile dimensions in those who attended the clinic. Outcomes: The primary outcome was to obtain accurate patient-reported satisfaction after inflatable penile implantation. Results: Within the timeframe, 542 patients underwent first-time IPP placements. Of that group, 322(n) completed the surveys, and 109 patients attended the clinic to compare preoperative vs postoperative dimensions. Of note, 67 (61.4%) and 54 (49.4 %) demonstrated enlargement in length and diameter, respectively. Conversely, 12 (11%) and 4 (3.7%) experienced a shortening in length and girth. We found 66 (60.5%) patients who complained about a penile size decrease after the intervention. The survey had a positive response in 93.1% of the cases. There were no statistically significant differences in positive responses concerning the variables investigated. The subpopulation analysis of the penile-sized group neither showed response variations. Clinical implications: The investigation allowed a better understanding of patient-reported satisfaction post-IPP placement. Strengths & Limitations: The performance of all the procedures in a high-volume center by a single surgeon limits its generalization. Conclusion: The overall results after IPP surgery are positive in most patients who underwent the procedure and the variables investigated did not influence the overall outcomes of the QoLSPP survey in the study.